The Myth Regarding the High Cost of End-of-Life Care - Aldridge, Melissa D. (Am J Public Health, 2015)
Health care reform debate in the United States is largely focused on the highly concentrated health care costs among a small proportion of the population and policy proposals to identify and target this “high-cost” group. To better understand this population, we conducted an analysis for the Institute of Medicine Committee on Approaching Death using existing national data sets, peer-reviewed literature, and published reports. We estimated that in 2011, among those with the highest costs, only 11% were in their last year of life, and approximately 13% of the $1.6 trillion spent on personal health care costs in the United States was devoted to care of individuals in their last year of life. Public health interventions to reduce health care costs should target those with long-term chronic conditions and functional limitations.